Food allergy risks and dining industry – an assessment and a path forward - Stankovich, Gabriel A.; Warren, Christopher M.; Gupta, Ruchi; Sindher, Sayantani B.; Chinthrajah, R. Sharon; Nadeau, Kari C. (Frontiers in Allergy, 2023)
Food allergies have increased in prevalence over the last few decades and continue to increase. Consumption of even trace amounts of common foods can cause a rapid allergic reaction (generally within minutes) which can be mild to severe to even life-threatening. For those with food allergies, eating at restaurants poses a risk of allergic reactions due to inadequate, inconsistent labeling of allergens in foods. Here, we review food labeling rules and practices in the restaurant industry and compare and contrast it with food labeling for prepackaged foods. We review global and US trends, and provide a brief historical overview. The paper describes the key legal and economic motivations behind restaurant food labeling. We describe novel risk-driven policies and new biotechnologies that have the potential to change food labeling practices worldwide. Finally, we outline desirable federal regulations and voluntary information disclosures that would positively impact the public health aspects of restaurant food labeling and improve the quality of life for people with serious food allergies.